Rationally Inattentive Behavior: Characterizing and Generalizing Shannon Entropy - Caplin, Andrew; Dean, Mark; Leahy, John (Journal of Political Economy, 2022)
We introduce three new classes of attention cost functions: posterior separable, uniformly posterior separable, and invariant posterior separable. As with the Shannon cost function, all can be solved using Lagrangian methods. Uniformly posterior-separable cost functions capture many forms of sequential learning and hence play a key role in many applications. Invariant posterior-separable cost functions make learning strategies depend exclusively on payoff uncertainty. We introduce two behavioral axioms, Locally Invariant Posteriors and Only Payoffs Matter, which identify posterior-separable functions as uniformly and invariant posterior separable, respectively. In combination, they pinpoint the Shannon cost function.